Sport and politics in Croatia - Athletes as National Icons in History Textbooks (Altre Modernità, 2015)
Strong relationship between sport and politics in everyday life is evident. Research on this topic has usually been concentrated on the relation between sport and nations. Despite that, research on the process of national identity (re)construction is still relatively rare. Therefore, as one aspect of that process, we have decided to do a research on the role of representation of sport in history textbooks. History textbooks represent an important tool in the construction and dissemination process of „official“ historical narratives in all states and societies, because the nation-states impose themselves as representatives of general public interest and they seek to retain control over school curriculum in order to validate the current system. When it comes to nation-states, one of the main goals of education is (re)construction of national identity among the youngest members of society. That was one of our initial theses in our analysis of the representation of sport in Croatian history textbooks for the final grades of primary and secondary schools in the period from 1918 to 2014. Our aim was to define the role of athletes and sport in general – both in the process of (re)construction of national identity and in the context of the process of modernization.
Keywords: sport; politics; Croatia; history textbooks; nationalism